2014
DOI: 10.1016/j.jcps.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of affect, processing goals and temporal distance on information processing: Qualifications on temporal construal theory

Abstract: According to temporal construal theory (Trope & Liberman, 2003, 2010, people are likely to evaluate a product on the basis of global, highlevel criteria (e.g., the intrinsic desirability of its features) if they consider it for future consumption but consider situation-specific (e.g., feasibilityrelated) criteria if they consider it for immediate use. However, this may be true only when people are unmotivated to assess the implications of all of the information they have available, and this motivation, in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Greater psychological distance implies seeing a bigger picture (Bar‐Anan et al, 2006; Liberman et al, 2002; Trope & Liberman, 2003; Trope et al, 2007). The construal level also might be related to happiness, because affective states shape the level at which people construe events too (Chen & Wyer, 2015; Williams et al, 2014). Being happier implies a focus on “why” (abstract level) rather than “how” (concrete level) to perform a task (Labroo & Patrick, 2009).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater psychological distance implies seeing a bigger picture (Bar‐Anan et al, 2006; Liberman et al, 2002; Trope & Liberman, 2003; Trope et al, 2007). The construal level also might be related to happiness, because affective states shape the level at which people construe events too (Chen & Wyer, 2015; Williams et al, 2014). Being happier implies a focus on “why” (abstract level) rather than “how” (concrete level) to perform a task (Labroo & Patrick, 2009).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Disclosing information in return for personalization is a social exchange, for which the reward (i.e., personalization) occurs after a time delay (Blau, 1964). This psychological distance causes the decision‐making process to be construed at an abstract level (Trope & Liberman, 2000, 2003), which in turn implies that affective states likely have a central role (Chen & Wyer, 2015; Williams et al, 2014). In particular, the pursuit of happiness is essential (Lyubomirsky et al, 2005) and perceived as more important than good health, being attractive, earning a high income, experiencing love, or finding a purpose in life (Diener & Oishi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although Messervey (2008) also found evidence that Asians' construal of events was less influenced by temporal distance than was Westerners' construal, other studies (Kim, Zhang, & Li, 2008;Yan, 2014;Chen & Wyer, 2015) have found effects of psychological distance on construal level using Hong Kong Chinese participants. Thus, it would be a mistake to conclude that Asians do not exhibit the effects implied by construal level theory, particularly when they are unmotivated to think extensively about the information they receive (Chen & Wyer, 2015). The effects of psychological distance among Asians may simply be less strong than it is among Westerners.…”
Section: Discussionmentioning
confidence: 99%
“…5. Les sens distaux (ex : ouïe, vue, odorat) permettent de traiter les stimuli qui sont spatialement éloignés de l'individu alors que les sens proximaux ne peuvent être utilisés que si les stimuli sont spatialement proches de ce dernier (Elder et al, 2017 Chang et Pham, 2018 ;Grant et Tybout, 2008 ;Huang et al, 2016 ;Jin et al, 2014 ;Keinan et Kivetz, 2008 ;Kivetz et Keinan, 2006 ;Kyung et al, 2010Kyung et al, , 2014Pizzi et al, 2015 ;Tan et al, 2019 Distance temporelle future Consommation d'un produit ou service dans un futur proche vs. lointain Basoglu et Yoo, 2015 ;Castaño et al, 2008 ;Chang et Pham, 2013 ;Chen et Wyer, 2015 ;Etkin et Ratner, 2013 ;Jeannot et Jolibert, 2013 ;Jin et He, 2013 ;Laran 2010a, Lee et al, 2017Lee et Zhao, 2014 ;Liberman et Trope, 1998 ;Trope et Liberman, 2003 ;Zhao et al, 2011 Lancement d'un nouveau produit dans un futur proche vs. lointain Balbo et Jeannot, 2015 ;Bornemann et Homburg, 2011 ;Jha et al, 2019 Lancement d'une campagne politique dans un futur proche vs. lointain Freitas et al, 2008 ; Recevoir un produit en cadeau dans un futur proche vs. lointain Lee et al, 2017 ;Williams et al, 2014 Faire un don pour une action sociale qui aura lieu dans un futur proche vs. lointain Choi et al, 2012 ;Czeizler et Garbarino, 2017 ;Ein-Gar et Levontin, 2013 ;…”
Section: Perspectives De Rechercheunclassified